Investigation of cardiac contractility signal among athletes from different sports - Sun, J.; Bu, B.; Su, Q. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: Previous studies show a close relationship between amplitude of the first heart sound (S1) and cardiac contractility. Based on this relationship, the present study used phonocardiography to evaluate the variations of cardiac contractility and cardiac contractility reserve. The amplitude of S1 directly reflects the variation of cardiac contractility. The purpose of this study was to obtain the relevant information of the cardiac reserve in individuals who participate in long-term exercise by comparing the Cardiac Contractility Change Trend (CCCT) among athletes in different sports and general college students. Further the study will also endeavour to identify the variation mechanism of the cardiac contractility signal among athletes in different sports.